Transient- and Native-Directing-Group-Enabled Enantioselective C–H Functionalization - Zu, Bing; Guo, Yonghong; Ke, Jie; He, Chuan (Synthesis, 2021)
In recent years, transition-metal-catalyzed enantioselective C–H bond functionalization using chiral transient directing groups (cTDGs) or native directing groups (NDGs) has emerged as a powerful and attractive synthetic approach to streamline the synthesis of chiral molecules. This short review focuses on recent advances on imine-based cTDGs strategies and native amine and carboxylic acid directed strategies for the asymmetric functionalization of various C–H bonds. We have endeavored to highlight the great potential of this methodology and hope that this review will inspire further research in this area.1 Introduction2 Transient-Directing-Group-Enabled Enantioselective C–H Functionalization2.1 Generation of Central Chirality2.2 Generation of Axial Chirality2.3 Generation of Planar Chirality3 Native-Directing-Group-Enabled Enantioselective C–H Functionalization3.1 Native Amines as Directing Groups3.2 Native Carboxylic Acids as Directing Groups4 Conclusions and Outlook
Keywords: asymmetric catalysis; enantioselective C–H functionalization; transient directing group; native directing group; synthetic methods